Comparison of innovative metallization approaches for silicon heterojunction solar cells. (September 2017) - Erath, Denis; Pospischil, Maximilian; Keding, Roman; Jahn, Mike; Lacmago Lontchi, Igor; Lorenz, Andreas; Clement, Florian
Abstract: Within this study, different metallization approaches were investigated and compared with respect to their applicability for silicon heterojunction (SHJ) solar cells. A printed line width of 34 µm with an aspect ratio of 0.59 was reached by double fine-line screen printing. In parallel, ink jet printing and its applicability regarding in-situ curing was evaluated. It was found that spreading of the ink is substantially reduced by choosing the optimum substrate temperature, enabling for a line width of 32 µm. Successful dispensing of a low-temperature silver paste was achieved by using a ten nozzle print head. By means of screen printed contact grids on both sides, solar cells with a conversion efficiency of 21.9 % were produced with industrial precursor wafers.